Solving Discrete Zero Point Problems - Gerard van der Laan; Dolf Talman; Zaifu Yang (Tinbergen Institute, 2004)
AbstractSee document.
Keywords: C61; C62; C68; C72; C58; 330; Discrete zero point; discrete fixed point; simplicial algorithm; triangulation; Analysis